Prototyping, customer involvement, and speed of information dissemination in new product success. Issue 4 (3rd May 2016) - Tih, Siohong; Wong, Kok-Kee; Lynn, Gary S.; Reilly, Richard R.
Abstract : Purpose: Rapid prototyping can potentially accelerate the entire process of new product development (NPD), enabling a high level of customer involvement and hence new product success (NPS). This study aims to examine the relationship between prototyping and NPS, and the moderating effect of customer involvement, as well as the influence of speed of information dissemination on customer involvement. Design/methodology/approach: Data were collected using the survey method through structured questionnaires. The key participants were management and team leaders from technology-based companies. Findings: The results indicate that prototyping positively correlates with NPS, particularly when customer involvement is high. The speed of information dissemination, both from customers and on competitive products, has a positive impact on customer involvement. Research limitations/implications: The study was limited by the undefined development stage of the prototype when offered for customer feedback. Future studies could focus on how customer involvement at each stage of prototype development affects NPS through a moderating effect. Practical implications: The study confirms that investing in prototyping equipment for NPD increases the probability of NPS. Information capturing customers' views and on competitive products in the market should be shared among the NPD teams. This could encourage better sharing of opinions and perceptions with customers about whether new products meet their wishes and expectations. Originality/value: This study demonstrates that customer involvement moderates the relationship between prototyping and NPS. The degree of customer involvement depended on the speed of response of the customers themselves and on how well competitive product information was disseminated within the NPD team.